(3fhQ GdTQb(B: (3ef ebJfjGJ GdOcJhQ SdWGf Hf eMeO GdbGSejs - Qasimi Collection (Sharjah Museums Department, 2013)
Exhibition catalog. Orientalist art in the collection of Sharjah Art Museum.
English
Keywords: N5198-5299 Private collections and collectors; Orientalist Collection; UAE